Pengaruh Problem Based Learning terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Dasar-dasar Teknik Mesin di SMK Negeri 1 Padang - Fikri, Muhammad; Syahri, Budi (Lembaga Yasin AlSys, 2025)
The subject of Basic Mechanical Engineering serves as a fundamental foundation for understanding various basic concepts that will be utilized in the practice and further development of mechanical engineering skills. However, based on observations, many students have unsatisfactory learning outcomes. This study aims to examine the influence of the Problem Based Learning (PBL) model on the learning outcomes of Grade X students in the Basic Mechanical Engineering subject at SMK Negeri 1 Padang. The research was conducted from October 7 to November 7, 2024, focusing on the elements of Occupational Health and Safety and Industrial Work Culture. The method used was an experimental study with two classes, namely the experimental class using PBL and the control class using conventional methods. Data were collected through a post-test consisting of 20 objective questions and 5 essay questions, as well as observations of students' learning activities. The results showed that the average score of the experimental class (83.22) was higher than that of the control class (75.86). In addition, the percentage of students who achieved passing scores in the experimental class was higher (29 students) compared to the control class (23 students). The use of the PBL model also increased students' interest and participation in the learning process, as evidenced by the increasing percentage of students' activities during the learning sessions. Based on the t-test, the t-value obtained was 2.457, which is greater than the t-table value 2.001 at a significance level of 0.05, indicating a significant influence of the PBL model on students' learning outcomes.